DAMPAK PUTUSAN MEDIASI KOMISI INFORMASI YANG BERKEKUATAN HUKUM TETAP TERHADAP KEWAJIBAN BADAN PUBLIK DALAM PERSPEKTIF HUKUM, POLITIK, DAN KOMUNIKASI - Demi Hamzah Rahadian (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
In a democratic rule-of-law state, the decisions of the Information Commission—including mediation agreements formalized as binding decisions—are final and legally enforceable. In practice, however, many public bodies ignore or delay the implementation of such decisions. This research employs a normative juridical method using conceptual, statutory, and case approaches, enriched by insights from political science and information-communication studies. The analysis covers the constitutional basis of the right to information, the normative construction of Law No. 14 of 2008 on Public Information Disclosure (UU KIP), and the position of Information Commission decisions within the Indonesian administrative justice system. From a political perspective, the article explores the power relations between public authorities and citizens and the implications of information disclosure for democratic quality. From an information and communication perspective, it discusses information as a source of power, the basis of public trust, and a tool of social oversight. The findings indicate that non-compliance by public bodies with mediation decisions of the Information Commission that have obtained permanent legal force constitutes a violation of the rule of law, the general principles of good governance, and citizens’ fundamental right to information. The absence of effective enforcement mechanisms, weak sanctions, and bureaucratic resistance are the main factors that undermine the enforceability of Information Commission decisions. The article recommends regulatory and institutional reforms, including stronger enforcement mechanisms through tighter integration with the Administrative Court (PTUN), clearer administrative and criminal sanctions, and the digitalization of information services to promote transparency and accountability.